Pesticide Labeling: Directions for Use - Frederick M. Fishel (EDIS)
This document describes the directions for use section of the pesticide label—usually the largest body of information found on most labels. Examples of typical directions for use statements are provided. This document is PI-104, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date March 2006.